Más allá del título y modo: transferencia de propiedad en el Perú a 40 años del Código Civil de 1984 - Arribas Irazola, Guillermo José (2024)
After 40 years of effectiveness of the 1984 Civil Code, the author reviews and questions the group of rules that regulate the transfer of property in Peru. Taking into special consideration the fact that the general rules of transfer of property in the book of Real Estate Law (‘Derechos Reales’) have not had any modification since its issuance in 1984, the author develops these rules together with those that complement our system of transfer of property, and the main discussions that have taken place on these matters in the last 40 years. In each case, the coherence of the system and the relevance of potential modifications are evaluated. The author proposes concrete reforms to this section of the Civil Code in order to ensure the adaptability of the rules of property transfer to new times.